Hambatan Penemuan Suspect TB Ditinjau dari Faktor Personal di Kabupaten Probolinggo Jawa Timur - ro'isah - ayu; Anies Anies; M. Sakundarno Adi; Nurjazuli Nurjazuli (Jurnal Kesehatan, 2020)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium Tuberculosis that is still being current public health problem. There are about 9-11.1 people suffering from tuberculosis. Indonesia becomes the third highest TB burden in the world with TB case detection rates which is still under 70%. These hidden cases will spread in the community. One of the factors that causes the low case detection is the number of suspect findings. The purpose of this study was to identify obstacles of finding TB suspect in terms of personal factors in the TB association members in Probolinggo Regency. The method of this study is qualitative with a phenomenological approach to explore social phenomena, values, experiences of life about behavior of TB suspect  discovery. The informants were 20 cadres of TB Association members. The data was collected by structured interview. The data analyzing used content analysis. The results showed that the obstacles in finding suspect of TB Association members in terms of knowledge found that generally, the cadres already knew about TB but lack of sputum removal techniques knowledge. In terms of personality, there was already an opened communication that explained about TB to the community, however TB is still considered as a horrible thing to be declared. The community has no awareness and feel embarrassed to check their disease.